2022
DOI: 10.1097/md.0000000000030023
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the most influential publications on vertebral augmentation for treating osteoporotic vertebral compression fracture: A review

Abstract: This study aimed to analyze the most influential publications on vertebral augmentation for treating osteoporotic vertebral compression fracture. The Web of Science database was searched using the key words "percutaneous vertebroplasty," "percutaneous kyphoplasty," "balloon kyphoplasty," "vertebroplasty," "kyphoplasty," and "vertebral augmentation." The top 100 publications were arranged by citations per year and descriptively and visually analyzed. The top 100 publications were cited 25,482 times, with an ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The core purpose of both is to insert bone cement into the fractured vertebral body ( 7 ). The treatment present optimal results only when it was used for “the most suitable patients” ( 8 ). VAPs have shown good uptake, and subsequent studies have shown the effectiveness of vertebroplasty procedures in controlling pain secondary to fracture conversely ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…The core purpose of both is to insert bone cement into the fractured vertebral body ( 7 ). The treatment present optimal results only when it was used for “the most suitable patients” ( 8 ). VAPs have shown good uptake, and subsequent studies have shown the effectiveness of vertebroplasty procedures in controlling pain secondary to fracture conversely ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cytokines resulting from the fracture also deteriorate the pain 6 . Osteoporotic vertebral compression fractures are a major issue in clinics, 7 as the prevalence rates of these fractures are increasing rapidly and are even highest among multiple types of osteoporotic fractures 8 . In addition, severe pain due to the osteoporotic vertebral compression fractures may increase mortality rates 9 …”
Section: Introductionmentioning
confidence: 99%
“…6 Balloon kyphoplasty (BKP) is a minimally invasive and effective treatment for vertebral fractures, and is widely used for the treatment of OVFs because it provides early pain relief and improves activities of daily living. 7,8 We previously demonstrated that intervertebral bridging osteophyte formation adjacent to the cephalic side of a fractured vertebra, as seen in DISH, is a poor prognostic factor for adjacent vertebral fractures and cement loosening following BKP for OVFs. 9 However, BKP also resulted ABBREVIATIONS BKP = balloon kyphoplasty; DISH = diffuse idiopathic skeletal hyperostosis; ODI = Oswestry Disability Index; OVF = osteoporotic vertebral fracture; PMMA = polymethylmethacrylate; ROC = receiver operating characteristic; VAS = visual analog scale.…”
mentioning
confidence: 99%